How the notion of “hybrid threat” is reshaping security. The case of migration and disinformation within the EU and its implications for the rule of law and democracy - Orrù, Elisa (Rivista italiana di informatica e diritto, 2025)
This article examines the emergence of the concept of “hybrid threats” in EU security policy, and its implications for fundamental principles of the rule of law and democracy. It discusses these dynamics by focusing on two exemplary phenomena that have been framed as “hybrid threats”: migration and disinformation. The article’s main argument is that characterising these phenomena as “hybrid threats” leads to an increased intertwining of civil and military, internal and external dimensions of security, resulting in a “hybridisation” of security policies. Ultimately, this shifts the emphasis of securitisation towards the extreme pole of “existential threats”. This places significant pressure on the fundamental principles of the rule of law, such as respect for fundamental rights and judicial control over executive powers, and also undermines democratic participation and the integrity of public discourse.“Minacce ibride” e ridefinizione della sicurezza. Le misure Ue nel campo della migrazione e della disinformazione e le implicazioni per lo Stato di diritto e la democraziaL’articolo esamina l’emergere del concetto di “minacce ibride” nelle politiche di sicurezza dell’Ue e le sue implicazioni per i principi fondamentali dello Stato di diritto e della democrazia. Il saggio analizza queste dinamiche concentrandosi su due esempi emblematici di fenomeni che sono stati progressivamente e sempre più decisamente caratterizzati come “minacce ibride”: la migrazione e la disinformazione. L’argomento principale dell’articolo è che definire questi fenomeni “minacce ibride” determina una crescente interconnessione tra le dimensioni civile e militare, interna ed esterna della sicurezza, con conseguente “ibridazione” delle politiche di sicurezza. In ultima analisi, tale processo sposta l’accento delle misure di sicurezza verso il polo estremo della risposta a “minacce esistenziali”. Ciò esercita una pressione significativa sui principi fondamentali dello Stato di diritto, quali il rispetto dei diritti fondamentali e il controllo giudiziario sui poteri esecutivi, e rischia di compromettere la partecipazione democratica e l’integrità del dibattito pubblico.